CEU légifelvétel - Budapest
Promotional video about Budapest. Contains aerial images with Heroes’ Square, the city center and St. István Basilica, the Danube, the bridges and the Parliament, as well as the Buda side with St. Geller Hill. Presentation from above of CEU’s main building on Nador street 11. Aerial footage with Kerepesi street and the CEU Residence and Conference Center.